2014
DOI: 10.5344/ajev.2014.14042
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Ripening Has Little Influence on Grapevine Cold Acclimation

Abstract: This four-year study tested whether the physiological demand of fruit ripening may interfere with grapevine cold acclimation in autumn or with midwinter hardiness. Three harvest time treatments were established in a mature vineyard of own-rooted Cabernet Sauvignon vines: clusters were removed after fruit set, at veraison, or after the first fall frost. Average yield of the late harvested vines varied from 4.2 to 5.1 kg/vine (7.5 to 9.2 t/ha) among years, and soluble solids varied from 23.4 to 25.6 Brix. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Seasonal variations were also expected since the temperatures in the days preceding sampling dates impact cold hardiness during maximum hardiness (Proebsting et al 1980). Partial deacclimation and reacclimation have been observed in every year of this study and have been noted previously (Keller et al 2014). These patterns were more frequent in Sauvignon blanc, particularly in the 2016/17 and 2017/18 dormant seasons, putting this cultivar at a greater risk of cold damage following the brief deacclimation periods.…”
Section: Sauvignon Blanc Clonessupporting
confidence: 87%
“…Seasonal variations were also expected since the temperatures in the days preceding sampling dates impact cold hardiness during maximum hardiness (Proebsting et al 1980). Partial deacclimation and reacclimation have been observed in every year of this study and have been noted previously (Keller et al 2014). These patterns were more frequent in Sauvignon blanc, particularly in the 2016/17 and 2017/18 dormant seasons, putting this cultivar at a greater risk of cold damage following the brief deacclimation periods.…”
Section: Sauvignon Blanc Clonessupporting
confidence: 87%
“…Activities that promote acclimation are a reduction in the nutrient use (for example, elimination of late compost applications; Westover 2006) after the fruitset to reduce the vegetative growth, elimination of irrigation post-veraison, avoiding top hedging at least three weeks before harvest, removing any grow-tubes around the trunks in mid-August to give enough time for the trunk acclimation, and thinning the excessive crop by cluster thinning at veraison (Rahemi 2016). However, Keller et al (2014) reported that the early fruit removal of vines with a commercially acceptable yield did not impact the cold acclimation on the grapevines tested in Washington state.…”
Section: Cold Climate Risksmentioning
confidence: 98%